A comparative study of operational engineering for environmental and compute-intensive applications - Giang Nguyen; Viera Šipková; Stefan Dlugolinsky; Binh Minh Nguyen; Viet Tran; Ladislav Hluchý (Array, 2021)
The study presented in this work deals with environmental and compute-intensive applications and their operational management aimed to achieve maximum effectiveness on high-performance systems. These applications, mainly compute-intensive modeling and simulations, are often required to deliver accurate forecasts having far-reaching effects on many facets of our society. The extreme growing amounts of observational data, along with remarkable advances in computing power and technology significantly improve the ability to model and simulate challenging issues. However, it is well known that designing, implementing as well as deploying such high-fidelity applications intended for running on compute systems is still time-consuming and challenging work for domain experts. In this study, we show that it is a systematic process requiring an expertise and skills in the scientific domain of interest, mathematics, and computer science. The study outcomes present and analyze successful benefits of high computational power for compute-intensive applications especially in the environmental domain.